2009
DOI: 10.1002/iub.177
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐tocopherol transport in the lung is affected by the apoE genotype—Studies in transgenic apoE3 and apoE4 mice

Abstract: SummaryApolipoprotein E (apoE) is a major constituent of lipoproteins mediating peripheral uptake of lipids including the lipid-soluble vitamin alpha-tocopherol (a-toc). In a recent study, we observed significant lower a-toc concentrations in the lung of apoE4 compared with apoE3 transgenic mice. In this study, we determined the mRNA levels of genes encoding for proteins centrally involved in the uptake, export, and degradation of vitamin E. Receptors of a-toc uptake including scavenger receptor B1 (SR-B1), LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Interestingly, APOE4 carriers seem to be less prone to vitamin D-deficiency, as extrapolated from population-wide APOE4 geographical distributions (37). However, animal studies using APOE4 transgenic mice have found significantly lower alpha-tocopherol levels in the lung compared to APOE3 controls (38). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, APOE4 carriers seem to be less prone to vitamin D-deficiency, as extrapolated from population-wide APOE4 geographical distributions (37). However, animal studies using APOE4 transgenic mice have found significantly lower alpha-tocopherol levels in the lung compared to APOE3 controls (38). …”
Section: Discussionmentioning
confidence: 99%
“…vitamin E concentration is lower in apoE4-than apoE3-targeted replacement mice, which is most likely due to the lower expression of LDL-receptor and related receptor classes mediating vitamin E uptake (103) . Furthermore, degradation of vitamin E may be increased in the apoE e4 genotype contributing to lower tissue retention and therefore possibly lower vitamin E status in peripheral tissues (104) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 98%
“…It is also reported that human plasma levels of a-tocopherol but not g-tocopherol are increased in male adults and children by the apolipoprotein A5 1131T.C gene polymorphism (15,16). In mice, apoE4 mice have lower plasma a-tocopherol than apoE3 mice (17).…”
mentioning
confidence: 99%